To solve the system of equations using substitution, we start with the following equations:
- \( x = y - 4 \)
- \( x + 8y = 2 \)
First, we will substitute the expression for \( x \) from the first equation into the second equation.
Substituting \( x \) in the second equation: \[ (y - 4) + 8y = 2 \]
Now combine like terms: \[ y - 4 + 8y = 2 \] \[ 9y - 4 = 2 \]
Next, add 4 to both sides: \[ 9y = 6 \]
Now, divide by 9: \[ y = \frac{6}{9} = \frac{2}{3} \]
Now that we have \( y \), we can substitute back to find \( x \): \[ x = y - 4 = \frac{2}{3} - 4 \] \[ x = \frac{2}{3} - \frac{12}{3} = \frac{2 - 12}{3} = \frac{-10}{3} \]
Thus, the solution is: \[ \left( \frac{-10}{3}, \frac{2}{3} \right) \]
Checking the response options:
- \( (-3 \frac{1}{3}, \frac{2}{3}) \) can be converted to an improper fraction: \( (-\frac{10}{3}, \frac{2}{3}) \).
So the correct response is: \[ \left( -\frac{10}{3}, \frac{2}{3} \right) \]
Thus the correct option from your responses is: \[ (-3 \frac{1}{3}, \frac{2}{3}) \]